(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The purpose of this research was to investigate the restvalue and post exercise situation (5, 30, 60minute) of athletes with heartrate, oxygen consumption, and blood lactic acid. The objectives for thisresearch were 20 volunteer Hockey players, from Barkatullah University’sdivision I and II Hockey players, whose average age was 21.6±1.83 years, averageweight was 79.6±8.05 kg, and average height was 184.5±4.19 cm. Duringexperiment, each subject rode the bicycle until completely exhaustion at aspeed of 60 RPM and power of 150W that will increase by 30W for every twominutes until they feel totally exhausted. Observed the changes of heart Rate,oxygen consumption and blood lactate from the physiological biochemical serumspecimens when the players were in resting state and recovery state afterexercising (5, 30, 60 min.). The indices were measured by the Polar heart raterecorder, Vmax29 analytical instrument, and blood lactate acid analyticalinstrument (YSI2300). All the information was analyzed by a single factor whichchanged and explained by the Schffee’ way, and the results as follow: 1. There was a significant differencebetween division I and division II with the heart rate (174.4±7.9 vs. 186.4±4.5bpm , P